EKSPLORASI TUMBUHAN HERBA BERMANFAAT OBAT OLEH MASYARAKAT TOLAKI DI DESA WATUKILA KECAMATAN LASOLO KABUPATEN KONAWE UTARA - AYU RESKI WAHYUNI AYU (Biology Department, Mathematics and natural science, Tadulako University, 2023)
The title of this research is “Exploration of Medicinal Herb Plants by the Tolaki Community in Watukila Village, Lasolo District, North Konawe Regency, Southeast Sulawesi. This research was conducted in September 2020 in Watukila Village, Lasolo District, North Konawe Regency, Southeast Sulawesi. The purpose of this study was to explore the types of herbaceous plants, the organs of herbaceous plants that are used as traditional medicine, and how to use and efficacy of herbaceous plants. The identification process was carried out at the Taxonomy Laboratory, Faculty of Biology Education, Halu Oleo University. The method used in this study is an exploratory and descriptive survey consisting of field surveys and interviews using a questionnaire. The results showed that there were 30 types of herbaceous plants from 20 families traditionally used as medicine. Organ leaves are most widely used as medicine with a percentage of 58%, the method used the most is boiled with a percentage of 53%.